Anticholinergics May Carry Significant Cognitive and Gait Burden in Parkinson's Disease. Issue 7 (29th August 2020) - Rajan, Roopa; Saini, Arti; Verma, Bhawna; Choudhary, Nishu; Gupta, Anu; Vishnu, Venugopalan Y.; Bhatia, Rohit; Singh, Mamta B.; Srivastava, Achal K.; Srivastava, Madakasira Vasantha Padma
ABSTRACT: Background: Anticholinergic drugs are associated with significant cognitive and other adverse events in older adults, including those with Parkinson's disease (PD). Anticholinergic effects are considered lesser in younger individuals and the burden and outcomes in younger patients with PD are unknown. Objectives: To determine the cumulative anticholinergic burden in a cohort of younger of patients with PD and to correlate the same with cognitive impairment and freezing of gait (FOG). Methods: We conducted a cross‐sectional study to identify the cumulative anticholinergic burden from medications prescribed to patients with PD. Two standard scales, the Anticholinergic Cognitive Burden (ACB) scale and the ACB score, were used to calculate the anticholinergic burden from prescriptions. We identified commonly prescribed drugs contributing to anticholinergic effects and correlated the cumulative ACB score with cognitive impairment (Movement Disorder Society–Unified Parkinson's Disease Rating Scale item 1.1) and FOG (Movement Disorder Society–Unified Parkinson's Disease Rating Scale items 2.13 and 3.11). Results: We recruited 287 patients with PD (68.9% male) with a mean age of 56.9 ± 11.8 years and a duration of symptoms 6.3 ± 6.9 years. Median ACB score was 4 (range 0–12). A total of 164 (58.4%) patients had total ACB score > 3. ACB score > 3 was independently associated with cognitive impairment (Odds Ratio, 2.55; 95% confidence interval, 1.43–4.53; P < 0.001) and FOG using patient‐reported measures (Odds Ratio, 3.192; 95% Confidence Interval, 1.68–6.07; P < 0.001) and objective measures (odds ratio, 2.41; 95% confidence interval, 1.27–4.6, P = 0.007). Conclusion: Patients with PD are exposed to significant anticholinergic burden from drugs prescribed for PD and non‐PD indications. Higher anticholinergic burden is associated with cognitive impairment and FOG even in younger patients with PD.